RESOLVING FARMERS-HERDERS CONFLICT IN NIGERIA: STATE FAILURE AND THE BRAZILIAN GRASS IMPORTATION PLAN - Williams Ehizuwa Orukpe (Romanian Journal of Historical Studies)
There are a plethora of development economics literatures shedding causal insight into why nations fail. But in Nigeria, there are little or no works explaining how state failure impedes development economics. This includes the formulation of plans, policies and strategies aimed at pushing back underdevelopment and resolving conflicts. This is because economic development needs industrial and social harmony to thrive. Nigeria’s farmersherders conflict is a classic example of how intra-sectoral and social conflict can impede development. Hence, this paper explored this problem in the context of state failure. It problematized Nigeria’s plan to import grass from Brazil as a farmer-herder conflict remedial impossibility and economic development illusion caused by state failure. The objectives of the paper are to demonstrate that sustainable agricultural development in Nigeria can only take place in an atmosphere of peace between herders and farmers; and to investigate the fingerprints of state failure on the public disaffection and distrust that undermined Nigeria’s plan to import grass from Brazil. The paper adopts the historical research methodology. Using the qualitative method of data analysis, it interpreted secondary materials. The findings of the study are: Nigeria’s neglect of its agricultural sector because of crude oil has a hand in its farmers-herders conflict; there was nothing economically wrong with Nigeria’s plan to import grass from Brazil as a farmer-herder conflict resolution strategy. The policy had the possibility of ending the conflict and improving Nigeria’s economy. But Nigeria’s failed political economy was the cog in the wheel that made it a development economics mistake.